The Local Wisdom of the Sasi Culture and Green Accounting (A Qualitative Approach from a Sustainability Perspective in Maluku Province) - Layn, Yuyun Yuniarti (Jurnal Ilmiah Manajemen Kesatuan, 2024)
This study explores the relationship between the local wisdom of the Sasi culture and green accounting within the framework of sustainability in Maluku. The Sasi culture, as a community-based natural resource management practice, reflects values of environmental preservation that align with modern sustainability principles. The research method used is descriptive qualitative with a phenomenological approach, involving interviews, observations, and documentation. The research informants consist of community leaders, local residents, village heads, and business practitioners. The results show that the Sasi culture plays an important role in environmental preservation and sustainable natural resource management. The integration of Sasi principles into green accounting enhances the quality of sustainability reporting and compliance with environmental regulations. These findings highlight the importance of combining traditional and modern approaches to create an inclusive sustainability model. The study recommends that the government, businesses, and communities adopt the Sasi culture in sustainability policies and explore further research opportunities in other regions.